Fluoride detox in early life as an initiative to eliminate Alzheimer's disease causing agents in Pakistan. - Saleem, Unsa; Tejani, Haniya; Ishfaque, Maheen; Umar, Muhammad; Hidayat, Ayesha (Nepal Journal of Neuroscience, 2024)
This investigation examines the association between fluorosis and Alzheimer's disease in the Pakistani population. Our findings suggest that elevated fluoride exposure leads to disrupted glutamate homeostasis, thereby increasing the likelihood of developing Alzheimer's disease. Globally, the prevalence of Alzheimer's disease exceeded 50 million cases in 2018, and Pakistan's sizable youth population is projected to be at heightened risk of dementia and Alzheimer's disease by 2050. The excessive fluoride consumption in Pakistan is attributable to the widespread use of fluoridated toothpaste, groundwater with elevated fluoride concentrations, tea, coffee, and cookware. To counteract this risk, we propose implementing fluoride-removing water filtration systems, the use of fluoride-free toothpaste, support for non-fluoridated agricultural practices, and promoting awareness programs aimed at reducing fluoride exposure and preventing Alzheimer's disease.